Overview of Student Knowledge,Attitudes, and Behaviors in Implementing Health Protocols During The Covid 19 Pandemi in UMJ Students 2021 - Arum Sri Ambarwati; Cut Nova Farhalida; Delika Puspita; Dhea Meditasari; Munaya Fauziah (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
Covid 19 is a new type of coronavirus that causes respiratory tract infections in humans ranging from cold coughs to more serious ones such as Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS) and is contagious. To stop the spread of covid 19, we must implement health protocols in our daily life. This study aims to determine the knowledge, attitudes, and behavior of health protocols from simple to Islamic concepts using qualitative methods with in-depth online interviews taken from 4 UMJ student informants. It was found that there were still students who still did not believe in the existence of Covid-19, knowing that the riskiest spread of covid came from droplets or sneezing, students mentioned 3M and 5M as the health protocols they applied, but the most effective way of prevention is to reduce mobilization in the community. outside the home, in terms of Islam students also know how to maintain cleanliness following religious teachings and pray that this pandemic will end soon. From this research, in implementing the health protocol, UMJ students have implemented it quite well and correctly. The knowledge, attitudes, and behavior of UMJ students in responding to the COVID-19 pandemics are good, starting with implementing 5M, always maintaining cleanliness, and from an Islamic point of view, they understand well.